As condições de trabalho de assistentes sociais nos Institutos Federais de Educação, Ciência e Tecnologia na realidade brasileira - Fernandes, Lígia da Nóbrega (2018)
The aim of this paper is to stand out the expressions of work conditions of social assistants in the Federal Institutes of Education, Science and Technology - IFET´s, based on a sample of five Brazilian states/regions. The study adopts the assumption implying that the present crisis of capital reproduction, the State management counter-reform and the changes in the working ‘world’ are giving rise to new ways of thinking, organizing and managing labor, and that the association of these universal determinants male set out particular incidences to the work conditions of the male and female social assistants, whose toil permits a mediation of student assistance policies inside IFET´s professional and technological education. The research basis involved a range of 146 social assistants, from a universe of 176 professionals, linked to 99 institutional units geographically spread in the states of Pará, Rio Grande do Norte, Minas Gerais, Rio Grande do Sul e Goiás, and that entered IFET´s so far as January 2015. The research development indicated that the structural and conjunctural crises of capital of the contemporary scene tries to recompose itself through fictitious profits which by themselves do not produce more value, looking for other means of fulfillment, as, for example, increasing the job insecurity. In this regard, it advances preferentially on the living labor with the unconditional aid of States-Nations which, for attending the intents of capitalist reproduction, develop adjustment policies for the sector of social security, the educational sphere, the working area and so on, whose reflects ‘invade’ work through phenomena like flexibilization, precariousness and intensification of work, lengthening of working hours etc. These universal elements common to the work conditions in the 21st century are indexed, with their particularities, on the work of the social assistants, which as employed persons began to act in the sphere of the inner public state of IFET, with dimensions and conditions of work analogous to those of the productive work, considering, among other possibilities, as the empirical field revealed, the professionals are gradually submitted to more and more controlled and extensive, intensified, tense day’s work with accumulated tasks, what certainly makes the professional work in the various IFET´s units more vulnerable to the condition of a precarious job.